A model for assessing personal blog quality - Muhammad Zain, Zuhaira (2012)
Technological breakthroughs have contributed to the Internet’s continuing growth, as witnessed in the significant growth of the blogosphere. Blogs may serve to provide information to accomplish important tasks or to keep readers informed on latest developments. However, the blogosphere has been crippled by its disorganized and uncontrolled growth, which affects the accuracy, context, representation, and accessibility of the medium. This will contribute to the problem of having poor quality blogs in the blogosphere given blog-readers’ easy accessibility. Consequently, blog has become a medium to distribute rumours and if the accusations involve the integrity of systems,institutions, and personalities, thus jeopardizing national security, it could lead to countrywide chaos. Various developmental domains, such as software engineering, website engineering, and information systems, have provided acceptable models to assess their product quality. However, some criteria of these models are irrelevant and inappropriate for assessing blog quality. In the blogosphere, researchers and bloggers have proposed guidelines, checklists, rules, and tips to create good quality blogs. Nevertheless, these criteria are only pertinent from the perspective of the blogger, not the readers. Thus, there is no evidence to show that the criteria are acceptable by the blog-readers. Many studies have been conducted to determine blog popularity, and credibility, but none of these focuses on blog quality. The aim of this research is to develop such a model to assess blog quality. First, the model was constructed by determining a set of criteria based on review of relevant literature and blogs. The acceptability of these criteria was subsequently measured through survey questionnaires sent to a sample of blog readers. A case study was conducted among the Personal Diary blog readers, the most popular blog category in Personal blog type, to validate the proposed model. The results show that the proposed model, comprising 49 criteria grouped into 11 families of features relevant to blog quality, was accepted and validated as a tool to assess blog quality. Second, case studies were conducted across five different Personal blog categories to analyse the importance of quality criteria. Our findings suggest that: (i) the importance of quality criteria or families of quality criteria depends on the respective blog category; (ii) certain quality criteria or families of quality criteria are more important for one blog category but less important for others; and (iii) some quality criteria or families of quality criteria are equally important for some blog categories but not for others. Third, a prototype of the Blog Quality Assessment Tool (BQAT) was successfully developed. Subsequently, a technology acceptance test using the Technology Acceptance Model (TAM) was conducted to investigate whether the prototype had been accepted by the blog readers. This study explored the impact of blog readers’ perceptions pertaining to ease of use, usefulness, attitude towards and intention to use the system to their liking. The findings indicate that the BQAT is an easy, effective, and useful method to help blog readers make a high quality assessment. This puts them in a positive frame of mind towards using the tool. Most importantly, blog readers suggest that bloggers should have the intention to participate in the blog quality assessment project. Hence, this research shows that the model can be used as a guide for blog readers to determine the quality of blogs visited. The model can also be used by bloggers to promote their readers’ satisfaction. This research not only implies that different blog categories should be designed using distinct quality criteria, in line with their relative importance to the respective category, but also recommends that blog categories should be assessed using different sets of quality criteria in accordance with their relative importance. Additionally, this research also provides a valid prototype of the BQAT that assists readers to assess blog quality. The prototype can also be used to manage and control a blog’s expansion, such that only high quality blogs continue to exist in the blogosphere.